Kelsey Hartmann: capstone - Hartmann, Kelsey, artist (Colorado State University. Libraries, 2019)
The artist's statement: My work is heavily focused on how the varying environment and multi-step process of a firing can affect the outcome of the work. It reflects my deeper search for how the environment we live in shapes and changes the final outcome of who we are and who we are meant to be. In a way these processes replicate my growth as an artist. In my collegiate career I have attended two universities. College has been a series of intense trials and tribulations. This final semester was the most productive, healthy, and passionate. The creative ways in which an artist is able to manipulate clay and intentionally shape the work, even after it has set in stone, allegorically representing the many changes I have seen in myself over the last 4 years. I proudly represent two different universities, which house two completely different environments. My self identity was forged through the trials, tribulation, and hardships of Arizona State University, creating an immovable rigidity in who I needed to be. After moving home I was able to see how a dramatic change, akin to the changes within ceramics, can change how I viewed the work. I was able to seek acceptance, belonging, and self-actualization at Colorado State University. This body of work is an artistic summation of my entire collegiate career. My focus on functional wares stems from my desire to feel useful and functional. At ASU I was paralized by my mental illnesses and legal entanglement. I have struggled with bipolar disorder and Post traumatic stress disorder. I see my emphasis on process in ceramics as a reflection of the processes I have endured to make myself healthy again through extensive therapy, medication, and the repair of family ties. These illnesses are still ongoing struggles for me but through my art I seek to relate to others struggling with mental health and illnesses. My goal behind this work is to elaborate a bit on the way in which the process creates a metaphor for a psychological experience and an experience of personal individuation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery